HUBUNGAN PEMANFAATAN PERPUSTAKAAN UNIVERSITAS NEGERI PADANG DENGAN HASIL BELAJAR MAHASISWA JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 221-227 , Ilmartha Dinata (CIVED, 2013)
The purpose of this research is to understand the correlation of the utilization of UNP’s library and the education performance of the students of Civil Engineering year 2010 of FT-UNP. This research is a descriptive research with the population of all students of Civil Engineering Department FT-UNP, Bachelor and Diploma in 2010, with 151 students. The sample is using proportional cluster random sampling method and the quantity of sample totaled with 110 students.The data is taken by doing interview with respondent that has been determined before, distributing questionnaire, and documentation in form of collecting information data like literature and archives. Data that has been collected then processed using statistic descriptive method by the SPSS application version 16.00. From the data above, it is concluded that there is no significant correlation between library utilization and the educational performance of students in Civil Engineering Department. This means that the utilization of library as the storage of knowledge still doesn’t have any significant correlation with the educational performance of Civil Engineering students in 2010 of FT-UNP. Key words : Utilization of Library, Study Result, Educational Performance